Acute Necrotizing Encephalopathy in Children: Insights and Outcomes from Iran: A Single Centre Original Research in Acute Necrotizing Encephalopathy of Childhood - Seilanian Toosi, Farrokh; Hashemi, Narges; Nejad Shahrokh Abadi, Reza; Mehdipour Arbastan, Ahmad; Akhoondian, Javad; Ashrafzadeh, Farah; Beiraghi Toosi, Mehran; Imannezhad, Shima; Maddahpour, Sara; Naseri, Maryam; Saeidinia, Amin; Kamali, Samaneh; et al. (Iranian Journal of Child Neurology, 2024)
Objectives Acute necrotizing encephalopathy of childhood (ANEC) is a rare, potentially life-threatening condition. This study aimed to identify clinical profiles and outcomes of ANEC while assessing the accuracy of severity scoring in the Iranian population. Materials & Methods The present study collected demographic, clinical, laboratory, and radiological data from children diagnosed with ANEC. Severity was measured using the ANE-Severity Score (ANE-SS), while outcomes were assessed with the Glasgow Outcome Score (GOS). This research analyzed the relationship between these scores and various parameters for statistical significance. Results Seven patients were included over three years, with an average age of 4.4±2.7 years (5 males). ANE-SS varied from moderate to high, with most patients experiencing moderate to severe disabilities, as indicated by the GOS. Significant correlations were found with initial serum magnesium levels, pupil light reactivity, and initial GCS score (P-value < 0.05). Conclusion Controlling initial magnesium levels may improve ANEC outcomes. Additionally, intact pupil light reactivity at admission was associated with a better prognosis.